Low-voltage varistor based on (Sn,Ti)O-2 ceramics - Bueno, Paulo Roberto [UNESP]; Cassia-Santos, M. R.; Simoes, LGP; Gomes, J. W.; Longo, Elson [UNESP]; Varela, José Arana [UNESP] (Amer Ceramic Soc, 2002)
A description is given of the nonohmic behavior obtained in (SnxTi1-x)O-2-based systems. A matrix founded on (SnxTi1-x)O-2-based systems doped with Nb2O5 leads to a low-voltage varistor system with nonlinear coefficient values of similar to9. The presence of the back-to-back Schottky-type barrier is observed based on the voltage dependence of the capacitance. When doped with CoO, the (SnxTi1-x)O(2)(.)based system presents higher nonlinear coefficient values (>30) than does the SnO2-based varistor system.